Latin American literatures in global markets : the world inside - Moraña, Mabel; Gallego Cuiñas, Ana (Leiden ; Boston : Brill, 2023)
"Market relations are changing not only the distribution and promotion of literary works but also their content, their language, and their social and political function. This book penetrates the intricacies of literary production, circulation and reception, focusing on some of the most original and representative authors of today such as Roberto Bolaño, Gabriela Cabezón Camara, Yuri Herrera, and Irmgard Emmelhainz, among others. The book also illuminates on the "materialitity" of literature and the strategies of literary marketing: festivals, book fairs, digitalization, and translation. Globalization and regional particularisms meet, then, in the symbolic territories of the literary world, and expose their dynamics and intrinsic negotiations"--
Introduction: A few turns of the kaleidoscope / Mabel Moraña -- Word and world: (re)inscriptions. The global alt-right as prefigured by Roberto Bolaño / Héctor Hoyos -- "En tanto poeta, ¡zas!, novelista": on Bolaño and Latin American poetry in the world literature system / Jorge J. Locane -- Rejoicing materiality: a geological writing by Gabriela Cabezón Cámara / Cristina Rivera Garza -- New media and new technologies in contemporary Latin American writing / Edmundo Paz Soldán -- The consecration and repositioning of a border writer: the phenomenon of the publishing market in the work of Yuri Herrera / Juan Rogelio Rosado Marrero -- Latin American genres, themes and writings in a global world. Latin American crónicas: the world-regional circulation of a local genre / Juan Poblete -- The archives of an exception to come: literature, cinema and the world in Irmgard Emmelhainz's El cielo está incompleto (2017) / Ignacio M. Sánchez Prado -- Beyond (Cuban) literature: global issues in Generation Zero / Catalina Quesada-Gómez -- The digital condition: algorithms, language, and imagination in Latin American digital literature / Carolina C. Gainza -- Literary culture and global consumptions. Materialities of literature in Latin America / Gustavo Guerrero -- Literary culture and spectacle: the boom in literary festivals in Latin America / Ana Gallego Cuiñas -- Measuring the consumption of bibliodiversity and foreign literatures in translation: supply and sales of translated books in Germany between 2007 and 2018 / Marco Thomas Bosshard -- Afterword: The Latin American writer and the global market / Ana Gallego Cuiñas.
Includes bibliographical references.
Description based on online resource; title from digital title page (viewed on January 19, 2023).
eBooks on EBSCOhost
Keywords: Latin American literature -- 20th century -- History and criticism; Latin American literature -- 21st century -- History and criticism; Literature publishing -- Latin America; Littérature latino-américaine -- 20e siècle -- Histoire et critique; Littérature latino-américaine -- 21e siècle -- Histoire et critique; Littérature -- Édition -- Amérique latine; Latin American literature; Literature publishing; Latin America; 1900-2099; Criticism, interpretation, etc; Essays; Literary criticism; Literary criticism; Essays; Critiques littéraires.